Women's preferences for antenatal care in Tanzania: a discrete choice experiment - Elizabeth M. Camacho; Rebecca Smyth; Valentina Actis Danna; Deborah Kimaro; Flora Kuzenza; Rose Laisser; Paschal Mdoe; Livuka Nsemwa; Happiness Shayo; Tina Lavender (BMC, 2022)
Abstract Background The stillbirth rate in Tanzania remains high. Greater engagement with antenatal care may help to reduce stillbirths. We investigated which characteristics of antenatal care clinics are preferred by pregnant women in Tanzania. Methods We conducted an unlabelled discrete choice experiment (DCE) with think-aloud interviews. Participants were pregnant women, regardless of parity/gestation, from the Mwanza and Manyara regions of Tanzania. We asked participants to choose which of two hypothetical antenatal clinics they would rather attend. Clinics were described in terms of transport mode, cleanliness, comfort, visit content, and staff attitude. Each participant made 12 choices during the experiment, and a purposively selected sub-set simultaneously verbalised the rationale for their choices. We analysed DCE responses using a multinomial logit model adjusted for study region, and think-aloud data using the Framework approach. Results We recruited 251 participants split evenly between the 2 geographical regions. Staff attitude was the most important attribute in clinic choice and dominated the think-aloud narratives. Other significant attributes were mode of transport (walking was preferred) and content of clinic visit (preference was stronger with each additional element of care provided). Cleanliness of the clinic was not a significant attribute overall and the think-aloud exercise identified a willingness to trade-off cleanliness and comfort for respectful care. Conclusion Women would prefer to attend a clinic with kind staff which they can access easily. This study suggests that exploration of barriers to providing respectful care, and enabling staff to deliver it, are important areas for future investment. The DCE shows us what average preferences are; antenatal care that is aligned with identified preferences should increase uptake and engagement versus care which does not acknowledge them.